2018
DOI: 10.4236/msce.2018.61005
|View full text |Cite
|
Sign up to set email alerts
|

Thermal, Mechanical and Rheological Properties of Low Density/Linear Low Density Polyethylene Blend for Packing Application

Abstract: Packaging is the subject of considerable commercial development by a variety of organizations around the world. In this study the mechanical, thermal and rheological properties were investigated for different blend ratios of low density polyethylene (LDPE) and linear low density polyethylene (LLDPE). The weight percent of the LDPEs used in the blends were 50, 60, 70, 80 and 90. The polymer blends were prepared in a twin screw extruder to produce a thin sheet (1-mm thickness) similar to the packaging grade. Ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…And because there is no long branch chain entangled with each other, the viscosity of LLDPE does not change much during processing, which makes LLDPE more suitable for film production than HDPE and LDPE. In addition, LLDPE can also be combined with a variety of antioxidants to prepare PE films with high ultraviolet stability, improving the photoelectric properties of the material [18].Finally, LLDPE can not only be used as a raw material for the production of films, but also as a filler to improve the mechanical properties of LDPE and PP [19,20].…”
Section: Applicationmentioning
confidence: 99%
“…And because there is no long branch chain entangled with each other, the viscosity of LLDPE does not change much during processing, which makes LLDPE more suitable for film production than HDPE and LDPE. In addition, LLDPE can also be combined with a variety of antioxidants to prepare PE films with high ultraviolet stability, improving the photoelectric properties of the material [18].Finally, LLDPE can not only be used as a raw material for the production of films, but also as a filler to improve the mechanical properties of LDPE and PP [19,20].…”
Section: Applicationmentioning
confidence: 99%
“…There is an abundance of published literature focusing on the use of recycled plastics, investigating polyolefin blends such as PE and PP (both virgin and recycled) [6][7][8][9][10][11][12][13][14][15][16], and studying the properties of various blends of virgin and recycled PE [17][18][19][20][21][22][23][24][25][26][27][28]. However, there is a noticeable gap in the literature characterising waste mixed plastics comprising of different grades of PEs and PPs of unknown composition.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Attar [17] investigated virgin LDPE/LLDPE (vLDPE/vLLDPE) blends. The study showed that incorporating vLLDPE into vLDPE results in higher mechanical properties than vLDPE alone.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits of LDPE/LLDPE blends in film applications, blend miscibility, and the miscibility of LDPE/LLDPE blends have certain effects on their properties, and few studies have been conducted on the miscibility of LDPE/LLDPE blends [ 3 , 4 , 5 , 6 ]. Most researchers have reported that LLDPE/LDPE blends are miscible at low LDPE contents and show immiscibility at higher LDPE [ 7 ]. In this study, the LDPE concentrations were kept low, and the differential scanning calorimetry (DSC) thermograms exhibited two overlapping peaks, which may be due to the phase separation of the LDPE and LLDPE components in the blended film after crystallization [ 8 ].…”
Section: Introductionmentioning
confidence: 99%